(3GdeTcdGJ GdYdejI aj GdbHV hGdJaJjT hGdOahY hGdHWdGf aj VhA Gdabg(B-(3CMcGe GdfbV(B-(3eMGce GdLfGjGJ hGdJYdjeGJ GdYGeI ddfjGHGJ(B. /s - (3gQLI, eLOj eUWais ((3GdbGgQI(B: s (3OGQ eMehO ddfTQ hGdJhRjY(B, s, 2003)
(3GdbHV heTcdGJ GdYdejI hGdOahY GdeJYdbI Hg(B- (3JYQja GdbHV heOdhdg(B- (3GdbHV hGdELQGAGJ GdeTGHgI(B- (3GdLgGJ GdeNJUI HEUOGQ ChGeQ GdbHV hMGdGJ EUOGQgG(B- (3GdbHV HeYQaI eCehQj GdVHW GdbVGFj(B- (3GdbHV HeYQaI SdWI GdJMbjb(B- (3GdbHV HeYQaI GdeMceI(B- (3GdeHGOF GdYGeI aj ChGeQ GdbHV(B- (3GdOahY GdeJYdbI HGdbHV(B- (3GdJaJjT heTcdGJg GdYedjI hGdOahY GdeJYdbI Hg(B- (3JYQja GdJaJjT hCfhGYg(B- (3JaJjT GdGTNGUs
Keywords: (3GdeYGedGJs; (3MSGHGJ GdbHVs